Quality of life and common mental disorders among female sex workers (Research, Society and Development, 2020)
Introduction: Prostitution has always been an activity related to taboos and stigmas, including in health services, where they usually focus only on reproductive and sexual clipping in women who perform this activity. Objective: To analyze the level of symptoms of Common Mental Disorders, quality of life and their correlations among female sex workers. Method: A cross-sectional, exploratory, quantitative study was conducted with 158 women, using the WHOQOL-Bref e and the Self Report Questionnaire (SQR-20), with p